Improved Scrum Framework using Agile Features (The International Journal for Scientific Research, 2023)
This paper provides an enhanced Scrum framework that combines some practices of eXtreme Programming (XP) approach in Scrum framework to gain quality software on time. XP and Scrum are two agile software development methods. While Scrum is focused on project management, XP is focused on Software development; nevertheless, they both can be used to participate in the development of any software project independently or together. This paper presents the main concepts, features, phases, artifacts, and roles of Scrum as well as a brief introduction to XP and its practices. In this paper, the researchers present how to combine some XP practices into Scrum activities. The researchers exploit the features and best practices of the two methods to propose an improved Scrum framework that includes guidelines for achieving each Scrum activity or process. So, the improved Scrum framework is more applicable than many previous attempts in this domain. The improved Scrum framework has been validated by a group of 40 experts and specialists in agile software projects.
Keywords: Scrum; Agile Methods Software Development; XP Approach; Agile Best Practices; Software Project